Identifying dimensions and components of organizational agility based on the development of human resources to provide a model of organizational agility in the Islamic Azad University of Tehran province - Soltani, Fatemeh; Nazem, Fattah; Imani, Mohammadnaghi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2022)
Background and purpose: This problem of how organizations can succeed in a dynamic and unpredictable environment is an issue that is known as the most important challenge in today’s world. Therefore, the purpose of this research was to identify the dimensions and components of organizational agility based on human resources development to provide a model of organizational agility in the Islamic Azad University of Tehran province. Methodology: In this regard, the statistical population of the research included all employees of the Islamic Azad University of Tehran province, which was about 6735. Among these, using Morgan’s table, Cochran’s formula, and multi-stage and proportional cluster sampling methods, 386 university employees were considered the sample size. The data collection method was based on a researcher-made questionnaire, research literature, and semi-structured interviews. Cronbach’s alpha coefficient of the research tool was calculated as 0.919. After distributing and collecting the questionnaires, the information was checked, and the hypotheses were tested using the structural equation modeling method and with the help of SPSS and LISREL software. Results: Finally, the research findings confirmed the five dimensions, strategic, information technology, human, organizational and cultural, as the dimensions affecting organizational agility based on the development of human resources. Conclusion: The research results showed that the strategic dimension has the highest average, and dimensions of information technology, human, organizational and cultural are placed in the next ranks. Finally, confirmatory factor analysis showed that dimensions of organizational agility based on human resources development explain up to 71.282% of the variance of existing indicators of organizational agility based on human resources development.